Retroperitoneal Bronchogenic Cyst: MRI Findings. (4th December 2013) - Castro, R.; Oliveira, M. I.; Fernandes, T.; Madureira, A. J.
Abstract : The authors describe a case of a retroperitoneal bronchogenic cyst in a 36-year-old female. She presented with abdominal pain, nausea, and vomiting. An MRI scan revealed an 8 cm cystic lesion in the left upper retroperitoneum, with intermediate signal on T2-weighted images, high signal on T1 weighted images, and lack of internal enhancement after gadolinium. After laparoscopic excision, the histology findings were compatible with a bronchogenic cyst, which is extremely uncommon in the retroperitoneum.